Pesantren di Era Globalisasi: Transformasi Modal Sosial dan Kewarganegaraan Komunitarian di Pondok Buntet Pesantren, Cirebon - Margi Wahono Wahono; Fegiano Wulung Alami (Universitas Negeri Semarang, 2026)
Globalization has significantly shaped education and religious life, posing challenges for Islamic educational institutions in Indonesia. Pondok pesantren are required to adapt to global change while maintaining their Islamic identity and values. This study examines the strategic responses of pesantren to globalization, focusing on curriculum integration, institutional development, technological adaptation, and cultural preservation. Using a descriptive qualitative approach with a case study at Pondok Buntet Pesantren in Cirebon Regency, the research analyzes forms of adaptation and innovation in response to contemporary demands through the lens of social capital and communitarian citizenship. The findings show that Pondok Buntet Pesantren responds proactively to globalization by integrating general and Islamic curricula, strengthening digital literacy, fostering moderate and civically responsible santri, and developing pesantren-based economic activities. Strong social capital reflected in solidarity, mutual cooperation (gotong royong), and trust in kyai leadership plays a vital role in sustaining the pesantren’s identity amid change. The study concludes that pesantren possess strong adaptive capacity as long as they remain grounded in inclusive and transformative Islamic principles, positioning them as both guardians of tradition and agents of social change in a globally oriented civil society.